(untitled) (Research, Society and Development, 2020)
Describe nursing care for patients with acute myocardial infarction undergoing coronary angioplasty as evidenced in scientific publications and analyze how nursing care provided to patients with acute myocardial infarction undergoing coronary angioplasty is carried out according to scientific publications. It is an integrative literature review study, with a qualitative approach. Data collection was carried out in March two thousand twenty in the databases of the Virtual Health Library (VHL), in the SCIELO, LILACS and Google academic databases, with the following descriptors present in the DECS: Nursing Care, Acute Infarction of the Myocardium, Angioplasty. As inclusion criteria, articles with full text, in Portuguese and Spanish, from two thousand fourteen to two thousand nineteen and related to the theme were chosen. The following were excluded: theses, dissertations, paid articles, newspaper articles and texts that were not related to the theme and literature reviews. At the end of the sample, nine articles were obtained, which were carefully analyzed. The study was divided into two categories in which the first shows the Profile of patients with Acute Myocardial Infarction and the Implications for Nursing care and the second deals with Nursing care for patients undergoing coronary angioplasty after Acute Myocardial Infarction. In view of the above study, it met the proposed objectives and proved to be of great relevance, as it may contribute to the understanding of nurses in the approach and care for patients with AMI undergoing coronary angioplasty.